Caracterização química e da matéria orgânica de solo em ambientes de veredas e lagos nas savanas do norte amazônico - Duarte, Ednalva Dantas Rodrigues da Silva (2018)
The environments of buriti lakes and trails (Mauritia flexuosa) are of great ecological importance for the environmental sustainability of the Roraima savanna. The objective in this work was to study soil organic matter (SOM) of lakes and buriti riparians of the Roraima savanna, chemical attributtes (pH, P, K+, Mg2+, Ca2+, Al3+, Al + H, C, and N), cation exchange capacity (CEC), sum of base, base saturation (V) and enzymatic activity of urease and cellulase. The study was carried in the municipality of Boa Vista, Roraima. The soils were collected in five reparians (Embrapa, Casai, Operário, Bom Intento and Bosco) and three lakes (Manaíra, CCA and Embrapa). The soil samples were submitted to chemical and biochemical analyzes, besides the extraction and fractionation of the humic substances. As soil samples were also characterized by CHN and 13C-NMR. The results were as follows: Histosols and Gleysols, strongly acidic, most environments presented pH range from 4.1 to 4.5, low available Ca2+, Mg2+, K+ and P contents, demonstrating the low fertility. The P available in the Bom Intento riparian was high and can be attributed due to the anthropic action. The values obtained for the sum of base were low, and for CEC it was high. The Al3+ contents were high and characterize the soils as allitic. The enzymatic activity presented variation between the environments lakes and buriti riparians, demonstrating that they are sensitive to anthropic action. The 13C-NMR spectra revealed that the aromatic organic compounds are predominant in the studied soils. Humin fraction (C-HUM) is predominant as fractions of the humic substances of these soils. According to the results, the soils of lakes and buriti trails of the savanna of Roraima can function as a source of C and are sensitive to anthropic action and require attention of policy actions aimed at the conservation of these areas.